Analisis mikrobiologi dan organoleptik mi basah hasil formulasi dengan penggunaan ekstrak bunga telang (Clitoria ternatea L.) sebagai pengawet alami dan antioksidan - Nurul Esti Handayani; Ika Dyah Kumalasari (AGROINTEK, 2022)
Clitoria ternatea is a promisiing material to as one of natural preservatives because it contains tannin compounds, carbohydrates, saponins, anthocyanins, flavonoids that has function as antibacterial and antioxidants. This study aims to determine the organoleptic and microbiological properties of wet noodle of Clitoria ternatea extract with various concentrations. This study used a completely randomized design (CRD) consisting of 4 formulations P1 (without extract), P2 (12,5 ml), P3 (25 ml), and P4 (37,5 ml). All formulations were carried out by organoleptic analysis with parameters of color, aroma, taste, hardness, stickiness, elasticity, and overall, then wet noodles with storage treatment of 0 hours, 12 hours, and 24 hours were subjected to microbiological tests. Wet noodles with the most preferred formulation at 0 hours, 12 hours, and 24 hours storage were subjected to chemical analysis tests. Wet noodles with data were analyzed by Analysis of Variance (ANOVA). If there is a significant difference between the treatments, it is continued with Duncan's test. The results showed that wet noodles with highest hedonic score ranged between 3.14-3.80 at 1-5 scale for color, aroma, taste, stickiness, elasticity, and texture was made using 25 ml butterfly pea extract indicated its preferability. This wet noodles proximate content also change during storage correlated to microbiological characteristics. The higher butterfly pea extract concentration, the higher bacteria growth inhbition capacity. Addition of butterfly pea extract had 63.07 % antioxidant activity. The result indicated that butterfly pea extract addition to wet noodles was preferable increased noodles shelf life while inhibited bacteria and fungi growth better than control, thus had potential as natural preservative for wet noodles